Effects and Mechanisms of Extracellular Vesicles in Different Models of Acute Kidney Injury - Weidong Wang; Jingyu Wang; Dan Liao (Stem Cells International)
Acute kidney injury (AKI) is a rapid decline in renal function caused by ischemia/reperfusion (I/R), renal toxic injury, and sepsis. While the precise molecular mechanisms underlying AKI are still under investigation, current therapeutic approaches remain insufficient. In recent years, there has been growing evidence that mesenchymal stem cells (MSCs) have great potential in accelerating renal repair after AKI in various preclinical models, while there has been extensive research on extracellular vesicles (EVs) as therapeutic mediators in AKI models, and they are considered to be superior to MSCs as new regenerative therapies. EVs are nanoparticles secreted by various types of cells under physiological and pathological conditions. EVs derived from various sources possess biomarker potential and play crucial roles in mediating cellular communication between kidney cells and other tissue cells by transmitting signal molecules. These vesicles play a direct and indirect role in regulating the pathophysiological mechanisms of AKI and contribute to the occurrence, development, treatment, and repair of AKI. In this review, we briefly outline the essential characteristics of EVs, focus on the multiple molecular mechanisms currently involved in the protection of EVs against different types of AKI, and further discuss the potential targets of EVs from different sources in the treatment of AKI. Finally, we summarized the deficiencies in the production and treatment of EVs and the current strategies for improvement.